2021
DOI: 10.21608/ejhm.2021.170510
|View full text |Cite
|
Sign up to set email alerts
|

Solid Organs Injuries in Blunt Abdominal Trauma Patients

Abstract: Background: Trauma is a major public health problem worldwide, morbidity and mortality in solid organ injuries (SOIs) following blunt abdominal trauma are often related to the severity of associated injuries. The management of SOIs depends upon the hemodynamic status of the patients. Hemodynamically unstable patients often require surgical management. Nonoperative management (NOM) is preferred in hemodynamically stable patients. Objective: This study was conducted to detect both incidence of solid organs injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In Egypt, the incidence of trauma is on the rise, primarily attributed to road traffic crashes (RTC), with males being disproportionately affected. Studies in Egypt found that males comprised 78–88 % of abdominal trauma cases [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, the incidence of trauma is on the rise, primarily attributed to road traffic crashes (RTC), with males being disproportionately affected. Studies in Egypt found that males comprised 78–88 % of abdominal trauma cases [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Trauma is a substantial global public health issue and a leading cause of death, hospital admissions, and long-term disability during the first four decades of life. Additionally, it ranks among the primary causes of mortality across all age groups [1,2]. Specifically, abdominal trauma ranks as the second leading cause of death among polytrauma patients, trailing head trauma as the primary cause and proceeding thoracic injuries [1].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal trauma is generally divided into two main categories: blunt or penetrating. The ramifications of blunt trauma can extend to any organ, and its consequences may not always be clinically apparent, necessitating a careful and thorough investigation [2]. The primary causes of blunt abdominal injuries often involve incidents like motor vehicle accidents, falls from elevated heights, and physical attacks, among other possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In hospitalized patients, abdominal solid organ injuries are associated with a mortality rate of approximately 5% [1]. Nonoperative management is the preferred approach for stable patients with isolated splenic injuries resulting from blunt trauma [2].…”
Section: Introductionmentioning
confidence: 99%